Application of the modeling method to the calculation of the probability of hitting a stationary target during the fire action of a tank squad in defense - Obradović, Zoran B.; Nikolić, Branislav B.; Popović, Goran P.; Gadzhalov, Nikolay D.; Krastev, Krastyu I. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction/purpose: The theory of direct firing of armored units deals with the calculation of the probability of hitting the target depending on the number of projectiles fired, in certain combat circumstances as well as under certain meteorological conditions. Successful performance of the combat task of armored units in defensive actions against stationary targets depends to the greatest extent on the effectiveness of fire of tank weapons. Under the tactical assumptions that define real combat conditions, i.e., that the attacking formation opens fire from small arms and anti-tank weapons, that the defense is organized in a timely manner on maneuvering ground and in optimal meteorological conditions, and that the tank squad opens fire while stationary, the scientific goal of the research is to determine the probability of hitting and destroying the target as closely as possible depending on the method of determining the distance to the target and the number of projectiles fired.Methods: Mainly applying the method of situation modeling in scientific research, the authors try to determine, as precisely as possible, the percentage of the probability of hitting (destroying) a stationary target, with the first, second, or third projectile.Results: The main scientific contribution of the research would be the determination of various quantitative indicators as significant parameters necessary for a successful design of defense operations of ground army units.Conclusion: By creating an appropriate model for a specific situation in order to solve a problem (combat task), it is possible to precisely determine the probability of hitting and the probability of destroying the target in relation to the number of projectiles fired, as well as the expected consumption of ammunition.
Keywords: firing theory; tank; tank squad; modeling